A Secure UTHM E-Voting System using Blockchain Technology - BIN RIZAUDDIN, SYARAFUDDIN SYAZWAN; AHMAD KHALID, SHAMSUL KAMAL (Applied Information Technology And Computer Science, 2025)
Voting for student leaders has been conducted regularly on campus. However, traditional voting methods that kept student records after votes in UTHM often suffer from illegitimacy including lack of transparency, security concerns of vote, and fraudulent practices. In this project, a secure e-voting system for UTHM using blockchain technology is proposed.  The e-voting system will implement robust security features, including encryption, role-based access control, smart contract, and authorization mechanisms. Each role in the system will be determined by the administrator, candidate and students, and will incorporate features that ensure the transparency and integrity of the voting process. Several experiments on the system's functionality and security have been conducted with potential users.  The results show that all functionalities achieve a 100% success rate. On the security sides, it achieves 78.6 % in input validation and error handling; 82.6% in sign up verification procedure; 100% on vote casting and counting procedures.  93% of the participants believe the proposed system is better than the existing system.  The results indicated a promising result for a reliable blockchain based e-voting system.